Profil pemprosesan kognitif pelajar pintar cerdas akademik di sekolah menengah - Rosadah Abd Majid,; Noriah Mohd Ishak,; Zalizan Mohd Jelas, (penerbit ukm, 2005)
Academically talented students were defined as students who exhibited talent in academic fields at a particular stage of development. Thirty-three academically talented students from a secondary school in the state of Selangor were involved in the study. These students had achieved grade A in all subjects sat for in a national standardized examination, the Lower Secondary Assessment (Penilaian Menengah Rendah-PMR). An adapted version of an instrument, the Cognitive Assessment System was used to measure the students’ cognitive processing namely; Planning, Attention, Simultaneous, and Successive. Multi dimensional scaling analysis was carried out on the data to reveal two prototypes of academically talented student in cognitive processing. Those who scored highly in Attention also scored highly in Successive. However, their scores in Planning and Simultaneous processes were low. Another prototype of academically talented students scored low in Attention and Successive processing. Nevertheless, their scores in Planning and Simultaneous were high. These findings propose to suggest two types of cognitive processing mechanisms among academically talented students. The first type of mechanism utilized Attention and Successive cognitive processing, when their Planning and Simultaneous cognitive processing were low. The second type of mechanism utilized Planning and Simultaneous processing when their Attention and Successive cognitive processing were low.